New Technologies of Laser Hardening of Parts of Fuel Equipment - Hnatenko, O. S.; Afanasieva, O. V.; Lalazarova, N. O.; Kurskoy, Yu. S.; Odarenko, E. N.; Sashkova, Y. V.; Ivanchenko, O. V. (Sumy State University, 2023)
Laser thermal hardening of steel (laser hardening) consists in heating a section of the steel surface above the phase transition temperature by laser radiation, followed by rapid cooling due to heat removal. As a result of this treatment, martensite is formed – a saturated solid carbon solution in α-iron. For laser hardening, gas CO2 lasers, solid-state (mainly Nd:YAG) and fiber lasers with a power of 0.5 kW or more are most often used. Optical systems for deploying and scanning the beam allow you to harden large areas of the surface with maximum efficiency. Not all products need processing of significant areas. Measuring and cutting tools, parts of fuel equipment, pump injectors are subject to significant abrasive wear of individual small areas. Less powerful lasers can be used to process them. There are no results of using low power pulsed lasers (up to 20 W) for surface hardening of steel products. The purpose of this work is to determine the modes of surface hardening of parts and tools made of carbon and alloy steels using low power pulsed solid-state YAG lasers. For laser hardening, a solid-state YAG laser with a power of 5 W (diode pumping, radiation wavelength = 1.064 µm, pulsed mode) was used. The use of a nonlinear crystal made it possible to obtain UV radiation from λ = 0.355 µm (third harmonic). Processing with single pulses and multi-pulse processing with short pulses were investigated. Thermal hardening was carried out on carbon and alloy steels of various compositions: 20, 45, У12, Р6M5, Р9, ШХ15, structural and tool steels for the purpose. The possibility of hardening by UV radiation was evaluated on steels 20, 45, У12 and ЩХ15. The efficiency of laser thermal hardening was evaluated by measuring microhardness. For surface hardening of products, where partial melting of the surface is possible, low-power pulsed lasers can be used. Laser hardening by UV radiation is a promising direction for thermal hardening of steels without surface melting. Hardening with a low-power laser is expedient for hardening parts of fuel equipment.
Нові технології лазерного зміцнення деталей паливної апаратури
Keywords: laser thermal hardening; low-power laser; single-pulse and multi-pulse processing; pulse duration; steel; martensite; fuel equipment parts; лазерне термічне зміцнення; лазер малої потужності; одноімпульсна та багатоімпульсна обробка; тривалість імпульсу; сталь; мартенсит; деталі паливної апаратури